DESAIN BENDUNG LANANG DI KABUPATEN GROBOGAN, JAWA TENGAH - Singgih, Rizky Herdianto; Nasrudin, Ryan Hermawan; Kodoatie, Robert J.; Edhisono, Sutarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Lanang Weir located at Penawangan District in Grobogan Regency, which has Non-Groundwater Basin Area hydrogeological characteristic. The river’s flow mostly come from interflow discharge beside from the groundwater flow. Soil layer which is able to store the water was Vadose or root zone only, so with this condition will prone to drought and flood when it precipitations just become runoff. Lanang Weir is a fixed weir, which will be built on Lanang River and the catchment area is 116.81 km2. This weir is watering 1,900 ha rice field area and designed with 50 years of return period of inflow discharge valued 548.08 m3/second and intake discharge valued 2.18 m3/second. Lanang Weir is design with specification rounded type of crest with height of 3,9 m, USBR type IV of stilling basin, equipped with sand trap, flushing way of sand trap, flushing gate, intake gate, and retaining wall. Construction of the Lanang Weir costs is around Rp 14 billion and scheduled for 28 weeks.